Trigeminal nerve dysfunction in patients with cranial base tumors - Polishchuk, Mykola; Voznyak, Oleksandr; Kaminskiy, Anatoliy; Oblyvach, Andrey; Sichinava, Vakhtang; Gudim, Maksim (Ukrainian Neurosurgical Journal, 2015)
Introduction. Impaired function of the trigeminal nerve is often the first and sometimes the only symptom of cranial base tumors. Materials and methods. Analysis of trigeminal nerve dysfunction before and after intervention in 38 patients operated on different cranial base tumors was performed. Totally 40 intervention were performed. There were 21 supratentorial (17 sphenoid wings meningiomas and 4 trigeminal neuromas), 8 subtentorial (2 acoustic schwannomas, 5 CPA meningiomas, 1 chordoma) and 9 sub-supratentorial (6 petroclival meningiomas, 3 trigeminal neuromas) tumors. Tumors were removed totally in 23 (60,5%), subtotally in 11 (29%) and partially in 4 (10,5%) cases. Results. Gasserian ganglion and trigeminal root decompression assured complete pain release in 27 patients. In 5 patients postop hemifacial hypesthesia was observed, followed by III nerve pulsy in 1, VI nerve pulsy in 2. There were no septic or fatal complications. Conclusions. Following the rules of scull base surgery and microsugical technic assured good postop result in this group of patients.